Horn growth rates of free-ranging white and black rhinoceros - D.J. Pienaar; A.J. Hall-Martin; P.M. Hitchins (Koedoe: African Protected Area Conservation and Science, 1991)
The intrinsic and observed anterior hom growth of white and black rhinoceroses is discussed. The effect of age and hom rubbing on hom growth is explained. Species and sex related differences in hom size and mass are investigated.